The suitability of foreign language teaching in childhood according to the CLIL approach: the foreign language teachers' attitudes - Smajla, Tilen (English Language Teaching Educational Journal, 2021)
This paper presents the results of a research into the foreign teachers' attitudes towards the first foreign language (FL 1) teaching according to the CLIL approach. The first foreign language teachers (FL 1 teachers) should have carried out their FL 1 lessons using the CLIL approach. The results of the twelve interviews: teachers agree upon the importance of the education process of teachers-to-be, for any teacher working at an early level should have completed a BA in class teaching and should have acquired a degree in the methodology of early language teaching. Most teachers who used the CLIL approach in the first year of its introduction (school year 2014â€“2015), refrained from it in the second year, or only used some elements of the CLIL approach, for they felt that it was impossible to follow the guidelines of the â€œhardâ€ CLIL. Consequently, they only used some elements or strategies of the CLIL approach, which some authors call â€œsoftâ€ CLIL. Although some teachers claimed to have encountered numerous obstacles in teaching according to CLIL, they nevertheless considered it to be a suitable approach in the FL 1 classroom.A well-prepared abstract enables the reader to identify the basic content of a document quickly and accurately, to determine its relevance to their interests, and thus to decide whether to read the document in its entirety.